O direito à regularização do IVA ( nos créditos incobráveis e nos créditos de cobrança duvidosa) - Pena, Carlos Alberto Rodrigues (2018)
Law No 66-B/2012, of 31 December 2012 (Portuguese State Budget Law for to 2013), has caused a significant change in how a creditor can proceed with a VAT (Value Added Tax) adjustment in respect of bad debts and doubtful debts. From then on, we have two simultaneous tax regimes: one for debts with expiry date until 31 December 2012; and another for debts with expiry date from 1 January 2013. The purpose of this study is to analyse the means afforded to creditors by which they can recover the tax of those debts, whether they are bad or doubtful, and to demonstrate the differences and similarities between the two systems, concluding, on whether the law reform has met its goal. As a starting-point, we make a brief foray into VAT as a European Community based Tax. As we shall see, VAT has tax-neutrality as one of its fundamental principles and, as a guarantor of that neutrality, the right to VAT deduction plays a key role and so we will examine the requirements and methods for exercising that right. Because we are in the field of VAT adjustments, their fiscal regimes are observed and, with a brief reference, those that are more common in practice. Finally, in designing the clarification of some concepts, we comment and identify solutions that can contribute to overcome the observed constraints.